Plagas de los cultivos de tagasaste (Chamaecytisus proliferus . fil.) Link áp. palmensis (Christ. Kunkel) en Canarias - Torres del Castillo, R.=700 1 Mendez, P.; Carnero, A.; Fernandez, M.
(Es, En)
ilus., 23 ref.
Keywords: CYTISUS PROLIFERUS; LEGUMINOSAS FORRAJERAS; PLAGAS DE PLANTAS; COCCOIDEA; ASPIDIOTUS NERII; PSEUDOCOCCUS; ESPAÑA